Science of spices and culinary herbs : latest laboratory, pre-clinical, and clinical sudies. - Atta-ur-Rahman (Science of Spices and Culinary Herbs Ser., 2020)
Many herbs and spices, in addition to their culinary use for taste,contain chemical compounds which have medicinal uses. For this reason, herbsand spices have been used for treating various ailments since ancient times.Modern scientific methods have enabled researchers to isolate bioactivecompounds from herbs and spices and perform chemical analyses, which can beused to develop medicines to treat different diseases. This book series is acompilation of current reviews on studies performed on herbs and spices. Scienceof Spices and Culinary Herbs is essential reading for medicinalchemists, herbal.